Low‐dose TNF augments fracture healing in normal and osteoporotic bone by up‐regulating the innate immune response. Issue 5 (14th March 2015) - Chan, James K; Glass, Graeme E; Ersek, Adel; Freidin, Andrew; Williams, Garry A; Gowers, Kate; Espirito Santo, Ana I; Jeffery, Rosemary; Otto, William R; Poulsom, Richard; Feldmann, Marc; Rankin, Sara M; et al.
Abstract The mechanism by which trauma initiates healing remains unclear. Precise understanding of these events may define interventions for accelerating healing that could be translated to the clinical arena. We previously reported that addition of low‐dose recombinant human TNF (rhTNF) at the fracture site augmented fracture repair in a murine tibial fracture model. Here, we show that local rhTNF treatment is only effective when administered within 24 h of injury, when neutrophils are the major inflammatory cell infiltrate. Systemic administration of anti‐TNF impaired fracture healing. Addition of rhTNF enhanced neutrophil recruitment and promoted recruitment of monocytes through CCL2 production. Conversely, depletion of neutrophils or inhibition of the chemokine receptor CCR2 resulted in significantly impaired fracture healing. Fragility, or osteoporotic, fractures represent a major medical problem as they are associated with permanent disability and premature death. Using a murine model of fragility fractures, we found that local rhTNF treatment improved fracture healing during the early phase of repair. If translated clinically, this promotion of fracture healing would reduce the morbidity and mortality associated with delayed patient mobilization.